1997
DOI: 10.1046/j.1471-4159.1997.68031304.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin‐Converting Enzyme Modulates Dopamine Turnover in the Striatum

Abstract: The effect of chronic inhibition of the angiotensin-converting enzyme on dopamine content and release in the striatum was investigated using in vivo microdialysis in awake, freely moving rats. Rats were treated for 1 week with the angiotensin-converting enzyme inhibitor perindopril (1 mg/kg) via the drinking water, whereas the controls were given water alone. One week after perindopril treatment, striatal dopamine dialysate levels in the treated group were markedly elevated compared with control values: contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(47 citation statements)
references
References 43 publications
1
45
0
1
Order By: Relevance
“…Central ACE plays an important role in catalyzing the release of dipeptide from a variety of substrates and can modulate dopamine activity [1,2]. It has long been considered a pathogenetic candidate for schizophrenic disorders; however, previous reports investigating ACE levels for schizophrenia have been inconsistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Central ACE plays an important role in catalyzing the release of dipeptide from a variety of substrates and can modulate dopamine activity [1,2]. It has long been considered a pathogenetic candidate for schizophrenic disorders; however, previous reports investigating ACE levels for schizophrenia have been inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Renin catalyzes the formation of angiotensin I, which is further converted into angiotensin II by angiotensin-converting enzyme (ACE) [1], which also catalyzes the degradation of substance P and other peptides. In addition, animal study has demonstrated that ACE mod- Ouyang/Wang/Hong/Cheng/Tsai ulates dopamine turnover in the midbrain [2]. Thus, the ACE gene may have pleitrophic effects within the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…This system has previously been thought to be involved in schizophrenia as well as other disorders [40,54,55]. Angiotensin II is a neurotransmitter that communicates with dopaminergic systems in the brain and is hypothesized to be important for normal thought processes [56,57].…”
Section: The Unbiased Screening Of the Genomementioning
confidence: 99%
“…11 The evidence about an involvement of the brain renin-angiotensin system in regulation of mood is based on several observations, as eg the co-localisation of angiotensin with dopamine synthesising neurones, 12 the fact that angiotensin converting enzyme (ACE) is involved in the metabolism of the neuropeptide substance P, which in turn is supposed to play a role in depression, 13 as well as the clinical observation that the application of ACE inhibitors in hypertensives might induce euphoric or depressive states. 14,15 Further, an animal study with angiotensinogen-deficient mice showed a reduction in depressive-like behaviour.…”
mentioning
confidence: 99%